Assessing the link between revenue management and performance: insights from the Italian tourism industry. Issue 1 (2014) - ,; ,
Abstract : Purpose – The aim of this paper is to analyse the role and scope of revenue management and its impact on performance of Italian tourism industry. The paper takes into consideration exogenous factors that may enable or prevent business success. Prior research shed light from different lens. Design/methodology/approach – Research design relies on an empirical analysis, information is gathered using a web survey. Variables are grouped into dependent (performance related items), independent and dummy, consistent with findings of existing literature. A questionnaire was e‐mailed to a range of companies according to their NACE Rev.2 codes. The conceptual model is developed considering prior analysis of the literature. Findings – This study provides new insights for practical business management operating in the tourism industry. Indeed, it clarifies the role of the revenue manager and shows its usefulness within SMEs. Research limitations/implications – This study was conducted in only one sector and one country (Italy) and considered only SMEs. Originality/value – Although interesting suggestions can be drawn by literature, to the best knowledge of the authors the empirical analysis is one of the few attempts to explore the topic in Italy in an extensive way.